The political economy of preferential trade in South Asia: the Indo-Sri Lanka free trade agreement - Mukherji, Rahul (International relations theory and South Asia, 2011)
The chapter explains why the Indo-Sri Lanka free trade agreement was signed in 1998 and came into force in 2000. It argues that changes in policy-relevant economic ideas and exogenous factors were important for the fructification of the free trade agreement. Rajiv Gandhi’s assassination by an active member of the Liberation Tigers of Tamil Eelam engendered unusual warmth in relations between the governments of Sri Lanka and India since the early 1990s. The Asian financial crisis precipitated the need for India to explore markets in the region when Southeast Asian and East Asian countries were reeling under the impact of a recession. India’s nuclear tests in 1998 and consequent economic sanctions only increased India’s desperation to search markets. India was willing to make the concessions that would make a free trade agreement with a smaller neighbour viable. This was a historic agreement not only because it was India’s first but also because it was with a South Asian neighbour.